Tacit knowledge in the software development process: profile of a research case study. (21st September 2021) - Dreyer, Hanna; Wynn, Martin
This article reports on a case study of knowledge development in the customisation of a cloud-based software product. The aim of the research project was to understand the creation and explicit exchange of tacit knowledge in this environment, focusing on both the individuals and the project team. A phenomenological approach was adopted, based on participant observation, meetings recording and analysis, and grounded theory. Unlike most tacit knowledge research, the goal was to capture the creation of knowledge in its moment rather than by the participants' recall of the phenomena. Results highlighted the significance of five different types of trigger in new knowledge generation, turning tacit knowledge into explicit knowledge. The article concludes that, despite the recent evolution of the software development environment in the digital age, a qualitative, informal, people centric approach to analysing knowledge development and exchange is still an effective means to securing positive outcomes in software development.